Non-catalytic glycerol dehydrogenation to dihydroxyacetone using needle-in-tube dielectric barrier discharge plasma - Grittima Kongprawes; Doonyapong Wongsawaeng; Peter Hosemann; Kanokwan Ngaosuwan; Worapon Kiatkittipong; Suttichai Assabumrungrat (Scientific Reports)
Abstract Glycerol, a by-product of biodiesel production, could be converted into various value-added products. This work focuses on its dehydrogenation to dihydroxyacetone (DHA), which is mainly used in the cosmetics industry. While several methods have been employed for DHA production, some necessitate catalysts and involve harsh reaction conditions as well as long reaction times. A needle-in-tube type dielectric barrier discharge (DBD) plasma technique for catalyst-free and environmentally-friendly glycerol conversion into DHA via dehydrogenation process was investigated using 0.1 M glycerol dissolved in deionized (DI) water at ambient temperature and pressure. The optimal condition was 60 W input power, 5 mm gap distance between the end of the needle and the liquid surface, and 0.5 L/min He flow rate. The highest DHA yield of 29.3% was obtained at 3 h with a DHA selectivity of 51.6% and glycerol conversion of 56.9%. Although the system allowed over 80% of glycerol to transform after 5 h, the DHA yield decreased after 3 h because the DHA product could further react with the reactive species in the plasma. The catalyst-free DBD plasma technique offers a simple and environmentally conscious method for DHA production via the dehydrogenation of glycerol.